PERAN NITRITE OXIDIZING BACTERIA DAN ACID PRODUCING BACTERIA DARI PERAIRAN WADUK CIRATA PADA PROSES KOROSI BAJA KARBON ST37 - Jasmine Ramadhani, Putri
Microbiologically influenced corrosion (MIC) is one factor that cause deterioration of Cirata hydropower’s infrastructure. From previous studies, it was observed that bacterial communities from 0.5 m depth induced corrosion at the rate of 5.66 mm/year on a laboratory scale and 0.28 mm/year on a field scale. There are MIC activities under these aerobic conditions by nitrite oxidizing bacteria (NOB) and acid producing bacteria (APB), but both of the corrosion behavior has not been evaluated specifically. This study aims to isolate NOB and APB from the Cirata Reservoir and determine the corrosion behavior of both communities. In the early stages, isolation and morphological characterization of the isolates were carried out. Then, screening APB in TSIA medium and NOB in LMM medium and determination of their corrosion behavior were done. The corrosion acceleration test was carried out by inoculating a consortium of 3 candidate isolates and then observing changes in pH, TDS, abundance of biofilm and planktonic bacteria, corrosion rate using the weight loss method, weight of biofilm & corrosion products, and final nitrate and sulfide concentrations using colorimetry every 3 days for 30 days in dark, static with condition of incubation: initial pH 7.8 and temperature 25°C. From the screening of 13 isolates, isolates F, G, and L were selected because they were confirmed to have NOB activity with nitrite residue values of the three isolates were 3.197 mM, 3.216 mM, and 2.9 mM, respectively, lower than abiotic control (8.883 mM). Isolates F and G also acted as APB, confirmed by the color change of TSIA to yellow. Isolate G was confirmed to induce corrosion on day 7 (18 mm/year) while isolate L on day 14 (13 mm/year). Isolate F wasn’t confirmed to induce corrosion. In the accelerated corrosion test, the maximum corrosion rate of F:G:L (2:1:100) treatment on the 3rd day of incubation was 13.8 mm/year while G:L (1:100) was 4.6 mm/year on the same day. Three cycles of biofilm were observed in both treatments with the abundance of planktonic bacteria decreasing by 2 log CFU/mL and the abundance of biofilm bacteria increasing by 3 log CFU/g. The maximum nitrate concentration in the F:G:L and G:L treatments, respectively, was 0.37 mM and 0.47 mM. A decrease in pH was also observed from 7.95 to 6.8 (G:L) and 8.1 to 7 (F:G:L). The conclusion of this study were isolates with NOB and APB activity were successfully isolated from the waters of the Cirata Reservoir. The corrosion behavior of the NOB and APB communities can be determined by the corrosion acceleration test with corrosive NOB and APB communities (G:L) can accelerate corrosion up to 10 times compared to the abiotic control, while the NOB community, non-corrosive APB, corrosive APB (F:G:L) accelerated the corrosion rate 3.3 times compared to the abiotic control.